THE EFFECT OF PROFITABILITY, ASSET STRUCTURE, AND SALES GROWTH ON CAPITAL STRUCTURE IN INDONESIA STOCK EXCHANGE IN 2014-2017 (In Manufacturing Companies, Industrial Sectors and Consumer Goods in the Pharmaceutical Sector) - Yofhi Septian Panglipurningrum; Adelina Dwiyani (STIE AUB Surakarta, 2019)
The purpose of this study was to determine the effect of profitability, asset structure and sales growth on the capital structure of manufacturing companies, industrial sectors and consumer goods in the pharmaceutical sector listed on the Indonesia Stock Exchange. The period used in this study is 4 (four) years, starting from 2014-2017. This study uses a quantitative approach. The population in this study is 10 pharmaceutical companies that have been listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling and obtained a sample of 8 companies. The data analysis technique usedis multiple linear regression. The results showed that partially Profitability (ROA / Return On Assets) had a negative and significant effect on capital structure indicated by a significance value of 0,000. The asset structure variable partially has a negative and significant effect on the capital structure indicated by a significance value of 0.006. And the variable sales growth (Growth) has a negative and not significant effect on the capital structure indicated by a significance value of 0.519. Simultaneously the variable profitability, asset structure, and sales growth have a negative and significant effect on the capital structure indicated by the F value of 0,000. The ability of variableprofitability, asset structure, and sales growth in explaining capital structure is 63.9% as indicated by the adjusted R square amount of 0.639 while the remaining 39.1% is influenced by other factors not included in the research model.